Determination of the pre-service science and classroom teachers' attitudes towards science teaching and technology and relationship between these attitudes - Ugras, Mustafa; Altunbas, Seda; Ay, Kemalettin; Cil, Erol (Elsevier Science Bv, 2012)
The purpose of this study, determine the pre-service science and classroom teachers. attitudes towards science teaching and technology. This study also purposed the determination of the pre-service science and classroom teachers/opinion about organization and using of computer, internet and technologies for educational purpose. The participants of this research included teacher candidates who were fourth year students in 2011-2012 academic years majoring in Science and Class Teaching Programmers at Firat University and Kafkas University, Faculty of Education, in Turkey. In this descriptive study, the technology attitude scale that developed by Erdemir, Bakirci and Eyduran and the attitude toward science teaching scale which was designed by Thomson and Shrigley and adopted to Turkish by Ozkan, Tekkaya and Cakiroglu were used as data collecting tools. SPSS 17 packet program and quantitative analyze techniques were used for the examination of obtained data. Rresults show that the pre-service science teachers have more positive attitudes toward science teaching than pre-service class teachers.
Cyprus International Conference on Educational Research (CY-ICER) -- FEB 08-11, 2012 -- Middle E Tech Univ No Cyprus Campus, CYPRUS
Keywords: Science Education; Technology; Teacher attitude; Science Teaching